2021
DOI: 10.1007/jhep08(2021)024
|View full text |Cite
|
Sign up to set email alerts
|

The axion-baryon coupling in SU(3) heavy baryon chiral perturbation theory

Abstract: In the past, the axion-nucleon coupling has been calculated in the framework of SU(2) heavy baryon chiral perturbation theory up to third order in the chiral power counting. Here, we extend these earlier studies to the case of heavy baryon chiral perturbation theory with SU(3) flavor symmetry and derive the axion coupling to the full SU(3) baryon octet, showing that the axion also significantly couples to hyperons. As studies on dense nuclear matter suggest the possible existence of hyperons in stellar objects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 104 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…State of the art axion mass calculations are now obtained by employing next-to-NLO (NNLO) χPT [15] or, alternatively, via lattice QCD techniques [16]. The axion-nucleon interaction Lagrangian instead has been derived in heavy baryon χPT up to NNLO [17,18]. Also CPand flavour-violating axion couplings have witnessed a resurgence of interest in the recent years, with new calculations based either on χPT or other non-perturbative approaches (see respectively refs.…”
Section: Introductionmentioning
confidence: 99%
“…State of the art axion mass calculations are now obtained by employing next-to-NLO (NNLO) χPT [15] or, alternatively, via lattice QCD techniques [16]. The axion-nucleon interaction Lagrangian instead has been derived in heavy baryon χPT up to NNLO [17,18]. Also CPand flavour-violating axion couplings have witnessed a resurgence of interest in the recent years, with new calculations based either on χPT or other non-perturbative approaches (see respectively refs.…”
Section: Introductionmentioning
confidence: 99%
“…In this brief review, I have only shown the O ( 𝑝 3 ) results including one-pion loops for the SU(2) case, while one-meson loops have also been studied for the SU(3) case (see Ref. [35]). However, the numerical results for these cases suffer from the fact that many of the involved low energy constants (especially but not exclusively the isoscalar ones) are entirely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Here I discuss recent developments in the study of the axion-nucleon coupling [29][30][31][32][33] in SU(2) heavy baryon chiral perturbation theory (HBCHPT) and the general axion-baryon coupling in SU(3) HBCHPT as developed in Ref. [34,35]. This is motivated from the fact that the axion-nucleon coupling plays a crucial role in determining the traditional axion window [18,19,36] 10 9 GeV 𝑓 𝑎 10 12 GeV,…”
Section: From the Qcd 𝜃-Vacuum To The Qcd Axionmentioning
confidence: 99%
See 1 more Smart Citation